Transforming agricultural extension in Eastern Africa through Climate Resilient Farmer Field Schools: Training update from the Climate Resilient Agribusiness for Tomorrow project - Osumba, Joab J.L.; Recha, John W.M.; Kabuka, Godfrey; Nzoka, Oscar; Wandera, Bright Asiimwe (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
There is a scientific consensus that climate variability and change is affecting food security for the growing population in Eastern Africa through increasing temperatures, changing precipitation patterns, and greater frequency of extreme weather events. Climate-smart and ecologically sustainable methods of agricultural production can help the region to adapt and mitigate the effects of climate change while increasing productivity and enhancing livelihoods. Climate-smart agriculture (CSA) could also provide the means to help policymakers, practitioners, private sector stakeholders, farmers and other critical value chain actors from the local, national to regional levels identify effective strategies to support the transformation of agricultural systems.